1978
DOI: 10.2136/sssaj1978.03615995004200010008x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clay Type and Content, Exchangeable Sodium Percentage, and Electrolyte Concentration on Clay Dispersion and Soil Hydraulic Conductivity

Abstract: The hydraulic conductivities and gradients along soil columns packed with montmorillonitic, vermiculitic, and kaolinitic soils adjusted to different levels of exchangeable sodium were determined at different salt concentrations. The data show that plugging of pores by dispersed clay particles is a major cause of reduced soil hydraulic conductivity for surface soils irrigated with sodic waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
163
0
14

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(191 citation statements)
references
References 0 publications
14
163
0
14
Order By: Relevance
“…One of the most important attributes required by landholders for effective soil use and management is that of clay content. This is particularly the case in the topsoil because (i) it greatly effects the water holding capacity and the hydraulic properties of a soil (Frenkel et al, 1978;Bresler et al, 1984;Jabro, 1992), (ii) it is related to the cation exchange capacity (Russell, 1973), and (iii) it influences the fertility and hence productivity (Davey, 1990). From the hydrological perspective knowledge of the subsoil and vadose zone clay content is also important because large amounts can reduce permeability, inhibit deep drainage, and potentially lead to waterlogged soil conditions (Triantafilis et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important attributes required by landholders for effective soil use and management is that of clay content. This is particularly the case in the topsoil because (i) it greatly effects the water holding capacity and the hydraulic properties of a soil (Frenkel et al, 1978;Bresler et al, 1984;Jabro, 1992), (ii) it is related to the cation exchange capacity (Russell, 1973), and (iii) it influences the fertility and hence productivity (Davey, 1990). From the hydrological perspective knowledge of the subsoil and vadose zone clay content is also important because large amounts can reduce permeability, inhibit deep drainage, and potentially lead to waterlogged soil conditions (Triantafilis et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Oliveira et al (2005) assessed the influence of W-D cycles on Water-Dispersible Clay (WDC) and showed that soils of reduced aggregate stability are more susceptible to the action of W-D on the WDC. According to Frenkel et al (1978), the plugging of pores by dispersed clay particles is the major cause of reduction in hydraulic conductivity and changes in suction head when the ion concentrations of soils are changed.…”
Section: Resultsmentioning
confidence: 99%
“…According to some scientific reports (Russo and Bresler 1977, Frenkel et al 1978, Oliveira et al 2005, water retention and movement can present differences due to 1) increases in the Na to Ca ratio of soil samples saturated with solutions containing these ions in their composition; 2) changes in water-dispersible clay as a result of modifications in the distribution of chemical elements inside the soil; and 3) alterations in soil porosity by dispersed clay particles caused by changes in the ion concentration of soils. In spite of these facts, no systematic studies on possible soil chemical element migrations during the SWRC evaluations were published in the soil science literature for tropical soils.…”
Section: Introductionmentioning
confidence: 99%
“…Vários autores (Frenkel et al, 1978;Rengasamy, 1983;Scheafer, 1994;Rodrigues Neto, 1996;Freire, 2001;Corrêa et al, 2003) observaram influência da mineralogia do solo na dispersão e floculação das argilas, mostrando sua alta significância sobre estes fenômenos. Rodrigues Neto (1996) Outro resultado que, de certa forma, também contrariou o que está apresentado na literatura foi o fato de o solo caulinítico (LVA) apresentar menor ADA-A, ADA-C e ADA-S que o solo hematítico (LV).…”
Section: Resultsunclassified